Interest In Learning Using Interactive Power Point - Sudarmono, Sudarmono; Norhayatun, Norhayatun; Hidayati, Herlina; Jayadi, Jayadi; Putri, Nikmah Sistia Eka; Dewy, Yuhani Mustika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The purpose of this research was to determine the difference in student interest in learning using PowerPoint interactive media among seventh-grade students at SMP Negeri 3 Mentaya Hilir Utara. This research is an experimental study using a one-group pre-test post-test approach. The population in this study consisted of all 32 seventh-grade students at SMP Negeri 3 Mentaya Hilir Utara. The data analysis technique used was the paired sample t-test. The result of analyzing this research data acquired a T score value of 3.157, a degree of freedom of 31, and a trust interval of 95% acquired a T table value of 2.03951. Because T count ≥ T table, H0 was rejected, which means that there is a difference in student interest in learning using interactive PowerPoint media among seventh-grade students at SMP Negeri 3 Mentaya Hilir Utara in the 2021/2022 academic year.